2022
DOI: 10.24200/jonus.vol7iss2pp120-146
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical Translanguaging in English as Second Language (Esl) Classrooms: A Survey of Existing Studies

Abstract: Background and Purpose: There has been a strong assumption on part of ESL practitioners to use target language for teaching of ESL. However, in recent years, translanguaging has gained significant importance in teaching of ESL. This systematic review concentrates on empirical studies that draw on translanguaging framework in ESL classrooms in diverse contexts. By using the guidelines provided by PRISMA, the current work sheds light on the recent plethora of literature available across the globe. This systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Academic investigators established that linguistic code-switching by bilingual students and dialectical shifting by students with dialects impacted phonological awareness, reading, spelling, composition, and fluency, particularly among students who spoke African American English, Regional Vernacular English, and Second Language English (Dougherty, 2023;García et al, 2017). Findings suggested that translanguaging, a process that encourages students to move fluidly between languages within a lesson, could bridge linguistic and cultural boundaries and improve the performance of bilingual students and others in comprehension, vocabulary, and writing (Atta & Naqvi, 2022). Providing a tech feature that allowed educators to record their voices to appropriately cue dialect-switching and translanguaging students and use Google Translate to infuse lessons with first-language instruction could help students overcome language barriers.…”
Section: Unique Technology Features For Spelling and Phonology Educatorsmentioning
confidence: 99%
“…Academic investigators established that linguistic code-switching by bilingual students and dialectical shifting by students with dialects impacted phonological awareness, reading, spelling, composition, and fluency, particularly among students who spoke African American English, Regional Vernacular English, and Second Language English (Dougherty, 2023;García et al, 2017). Findings suggested that translanguaging, a process that encourages students to move fluidly between languages within a lesson, could bridge linguistic and cultural boundaries and improve the performance of bilingual students and others in comprehension, vocabulary, and writing (Atta & Naqvi, 2022). Providing a tech feature that allowed educators to record their voices to appropriately cue dialect-switching and translanguaging students and use Google Translate to infuse lessons with first-language instruction could help students overcome language barriers.…”
Section: Unique Technology Features For Spelling and Phonology Educatorsmentioning
confidence: 99%